2006
DOI: 10.1002/anie.200503709
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of the N2 Triple Bond by the Ti Dimer: A Route to Molecular Materials for Dinitrogen Activation?

Abstract: The Ti dimer is fairly weakly bound, but highly reactive, and completely cleaves the strong N2 triple bond in just one step without activation energy (see scheme; Ti red, N blue). In contrast, a Ti atom in its ground electronic state does not react with N2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 21 publications
1
57
1
Order By: Relevance
“…[103] In the course of this reaction, the NÀN triple bond is completely cleaved with the formation of a four-membered, planar [Ti 2 N 2 ] ring compound. The experiments have been repeated with different dinitrogen isotopomers.…”
Section: Groupmentioning
confidence: 99%
“…[103] In the course of this reaction, the NÀN triple bond is completely cleaved with the formation of a four-membered, planar [Ti 2 N 2 ] ring compound. The experiments have been repeated with different dinitrogen isotopomers.…”
Section: Groupmentioning
confidence: 99%
“…The reactivity of metal atoms and dimers toward N 2 was reviewed in 2006 . Sc 2 , Y 2 , La 2 and Ti 2 react spontaneously with N 2 to form Sc 2 N 2 and Ti 2 N 2 to break the strong triple bond (see Scheme ) . One of the bands of the Ti 2 N 2 product in the IR spectrum is shown in Figure .…”
Section: Metal Atom Clustersmentioning
confidence: 99%
“…One of the bands of the Ti 2 N 2 product in the IR spectrum is shown in Figure . The bands due to each isotopologue are split into three components due to the polycrystalline matrix host (“matrix splitting”) . Ti 2 N 2 reacts further with an excess N 2 to give presumably [Ti 2 N 2 (μ‐N 2 )(N 2 ) 8 ] (see Scheme ) .…”
Section: Metal Atom Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several dinitrogen titanium sandwich complexes have been synthesized [53][54][55], but none of them were successful for the hydrogenation of N 2 . Recently, a matrix isolation study showed that the ''naked'' Ti 2 dimer cleaves the NaN triple bond of N 2 and forms (TiN) 2 species without a significant energy barrier [56].…”
Section: 4mentioning
confidence: 99%